Developing libraries in Brazil, with a chapter on Paraguay, de Cavan McCarthy - Nery da Fonseca, Edson (Revista de Biblioteconomia de Brasília, 1975)
MCCARTHY, Cavan. Developing libraries in Brazil, with a chapter on Paraguay. Metuchen, N.J.: Scarecrow Press, 1975. 207 p. LC74-23681. ISBN 0-8108-0750-5.